2017
DOI: 10.3233/xst-17247
|View full text |Cite
|
Sign up to set email alerts
|

Subinguinal microsurgical varicocelectomy with intraoperative microvascular Doppler ultrasound leads to the pain-free outcome after surgery

Abstract: Subinguinal microsurgical varicocelectomy is an effective method to treat painful varicoceles. With the assistance of Doppler Ultrasound monitoring, greater numbers of vessels were identified and a better outcome of pain resolution was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…The differential in number of ligated veins was reported in all of the studied studies [5][6][7][8][9]. The difference in mean number of ligated veins between the group of subinguinal microsurgical varicocelectomy with Intraoperative Vascular Doppler Ultrasonography compared to the group of subinguinal microsurgical varicocelectomy without Intraoperative Vascular Doppler Ultrasonography was statistically significant (MD 0.94; 95 percent CI 0.62 -1.26; p < 0.00001) as shown in Figure 3.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 69%
See 2 more Smart Citations
“…The differential in number of ligated veins was reported in all of the studied studies [5][6][7][8][9]. The difference in mean number of ligated veins between the group of subinguinal microsurgical varicocelectomy with Intraoperative Vascular Doppler Ultrasonography compared to the group of subinguinal microsurgical varicocelectomy without Intraoperative Vascular Doppler Ultrasonography was statistically significant (MD 0.94; 95 percent CI 0.62 -1.26; p < 0.00001) as shown in Figure 3.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 69%
“…Finally, the quantitative analysis of this study included 5 papers that met the inclusion criteria. In our meta-analysis, we analyzed 5 papers [5][6][7][8][9] that compared the use of IVDU against no IVDU in subinguinal microsurgical varicocelectomy procedures. Three RCTs and two observational studies made up our individual investigations.…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that the definite relationship still needs to be clarified ( 24 ). Although conflicting results are present, it is still considered that individual sperm parameter is not diagnostic for infertility, as a normal count of motility may not result in a higher chance of pregnancy ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Таким образом, пациенты в 1-й группе имели лучшие результаты в разрешении болевого синдрома (p = 0,033). Время операции, осложнения и частота рецидивов не различались [21].…”
Section: обзорная статья / Reviewunclassified